Advanced methods for measurement uncertainty evaluation - Zakharov, I.; Botsiura, O. (MMA-2022, 2022)
Disadvantages of the law of propagation of uncertainty underlying the implementation of the model approach in the GUM are analyzed. Advanced methods for implementing a model approach to measurement uncertainty evaluation are described, which allow eliminating the shortcomings of the GUM uncertainty framework: the law of propagation of distributions, the kurtosis method, the law of propagation of expanded uncertainty, the law of propagation of observational results for reliable evaluation of type A uncertainty for correlated and uncorrelated measurement results of input quantities.
Keywords: model approach to measurement uncertainty evaluation; Monte Carlo method; kurtosis method; the law of propagation of expanded uncertainty; reduction method; transposition method